Diseño de un sistema de costos para la fábrica de muebles el Mega Dorado, cantón Latacunga, provincia de Cotopaxi - Soto Segovia, Jessica Mishel (2022)
Business competition stay into market, to generate profit, and satisfy needs is tough, therefore, several organizations apply financial matters and human resources, what promote their stability; managers use accounting and costing as a strategy, since they reflect detail and objectively the monetary situation. The entitled project "A Cost System design for The Mega Dorado Furniture Factory, Latacunga Canton, Cotopaxi Province" has as purpose to determine the production cost by identifying its elements in each furniture piece, such as the Alexa comfortable bar, Isac weekly, Perla dining set, Valentina living room set with bar, Lorens cabinet, and Heydi bunk bed, which are required by consumers; since when calculate, empirically, it was reasonably unknown the sale price, as well as, the profits generated by each item. The used methodology has a quantitative approach, because it was applied mathematical methods, through a sequence, what led to specific results, which this case was the production cost determination and its impact onto financial statements; as related to research techniques, are used an interview directed to the manager, and surveys to the accountant, production manager and winemaker; giving as results, what the articles total empirical value under analysis was $3.271,00, while the real value is $2.877,08, at generating a $393,92 difference into determining the cost, which allowed increasing the elaborated products and competitiveness profit margin in the market.